Pharmacological thiamine levels as a therapeutic approach in Alzheimer's disease - Gibson, Gary E.; Feldman, Howard H.; Zhang, Sheng; Flowers, Sarah A.; Luchsinger, José A. (Frontiers in Medicine, 2022)
Graphical Abstract Summary of the study.